Visual search differs but not reaction time when intercepting a 3D versus 2D videoed opponent - Lee, M. J. C.; Tidman, S. J.; Lay, B. S.; Bourke, P. D.; Lloyd, D. G.; Alderson, J. A. (Journal of Motor Behavior, 2013)
The authors aimed to identify differences in (a) visual search and (b) reaction time when athletes sidestepped to intercept 2D versus 3D videoed opponents. They hypothesized that participants would (a) fixate on different parts of the opponent's body and (b) react quicker when responding to the 3D versus 2D opponent due to the added depth cues. A customized integrated stereoscopic system projected the video stimuli and synchronously recorded the gaze and motor behaviors of 10 men when they responded to two- (2D) and three-dimensional (3D) opponents. The number and duration of gaze fixations were coded according to locations on the opponent's body (head, shoulders, arms, trunk, pelvis, legs) or otherwise (other). Mediolateral pelvic movement was used to infer reaction time. Participants spent 16% less time fixating on the trunk and 23% more time outside the 3D opponent's body compared with the 2D stimulus. No reaction time differences were found. Although participants fixated less on the 3D opponent's body and, by inference, invested less perceptual processing toward interpreting the opponent's movements compared with the 2D condition, they performed the interception task equally fast in both conditions. Three-dimensional depth cues may provide more meaningful information per fixation for successful task performance.